2017
DOI: 10.1155/2017/5831020
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Genome-Wide Association Study in Postmenopausal Mexican-Mestizo Women Implicates the RMND1/CCDC170 Locus Is Associated with Bone Mineral Density

Abstract: To identify genetic variants influencing bone mineral density (BMD) in the Mexican-Mestizo population, we performed a GWAS for femoral neck (FN) and lumbar spine (LS) in Mexican-Mestizo postmenopausal women. In the discovery sample, 300,000 SNPs were genotyped in a cohort of 411 postmenopausal women and seven SNPs were analyzed in the replication cohort (n = 420). The combined results of a meta-analysis from the discovery and replication samples identified two loci, RMND1 (rs6904364, P = 2.77 × 10−4) and CCDC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
12
0
1
Order By: Relevance
“…The pilot GWAS with TC, Low-Density Lipoprotein cholesterol (LDL-c), HDL-c, glucose and TG serum levels was carried out using the EPACS Genome Analysis tool as follows: we performed a quantitative linear Wald Test model using residual inverse normal transformation of age, body mass index (BMI) and two ancestry principal components (ancestry correction). The study design and methodology are described in detail elsewhere [ 29 , 30 ]. Briefly, the median age of the cohort was 61 years (55–68), median BMI was 27.5 (25.3–34.3) and 68.2% had MetS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pilot GWAS with TC, Low-Density Lipoprotein cholesterol (LDL-c), HDL-c, glucose and TG serum levels was carried out using the EPACS Genome Analysis tool as follows: we performed a quantitative linear Wald Test model using residual inverse normal transformation of age, body mass index (BMI) and two ancestry principal components (ancestry correction). The study design and methodology are described in detail elsewhere [ 29 , 30 ]. Briefly, the median age of the cohort was 61 years (55–68), median BMI was 27.5 (25.3–34.3) and 68.2% had MetS.…”
Section: Methodsmentioning
confidence: 99%
“…The present study is part of a large-scale genetic study to identify genetic variants affecting bone mineral density (BMD) and related quantitative metabolic traits in the Mexican population [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…found a LS-BMD associated signal within LOC100506136 in a Mexican-Mestizo cohort [60]. These studies suggest that this lncRNA could be involved in osteoporosis pathogenesis.…”
Section: Accepted Manuscriptmentioning
confidence: 57%
“…Recent GWAS and candidate gene studies have found a relationship between different genetic variants in SOX6 regions and osteoporosis phenotypes (femoral neck, lumbar spine and wrist BMD) [22][23][24][25][26][27][28][29][30][31] . Interestingly, the rs7117858 SNP located downstream of the SOX6 gene have been reported to be associated with BMD in Caucasian and Chinese populations [23][24][25][26]32 .…”
Section: Introductionmentioning
confidence: 99%